Evaluation of anesthetic, locomotor, and sedative scores for lumbosacral epidural analgesia using bupivacaine and bupivacaine-dexmedetomidine in sheep - Sultan Fadel Al-Haid; Sayed Fathi El-Hawari; Adel Ibrahim Almubarak; Zakriya Ali Al Mohamad; Sherief Mohamed Abdel-Raheem; Hazem Assem Youssef; Ahmed Mohamed Abdallah (Open Veterinary Journal)
Background: Lumbosacral epidural analgesia is one of the most important techniques for sheep anesthesia and is frequently used for surgery in caudal body regions.